Trimester-specific reference intervals for blood lipid levels and their associations with adverse pregnancy outcomes in Southeast China - Lili Yang; Zhaozhen Liu; Jiayi Chen; Chong Miao; Qingxiu Li; Jinying Chen; Wenjuan Liu; Haiyan Gao; Wei Li; Zhengqin Wu; Bin Sun; Yibing Zhu; et al. (Lipids in Health and Disease)
Abstract Background Trimester-specific reference intervals (TSRIs) for maternal lipid profiles should be determined, and the impact of dyslipidemia on adverse pregnancy outcomes (APOs) should be estimated. Methods Data from 25,081 pregnant women in a large Southeast Chinese cohort were collected. Serial lipid profiling was performed throughout gestation, with measurements obtained during the first, second, and third trimesters, as well as within 24 h of delivery. The truncated maximum likelihood (TML) method, the Hoffman method, and inverse modelling were employed to establish TSRIs for lipids, with TML as the primary method. The associations of dyslipidemia with APOs were investigated by logistic regressions within the setting of TSRIs for various lipids. Results The TSRIs established by the TML method were as follows: 3.36–6.06, 4.19–7.89, 4.60–8.97, and 4.41–8.79 mmol/L for total cholesterol; 0.66–2.32, 1.11–3.75, 1.49–4.77, and 1.61–6.14 mmol/L for triglycerides; 1.42–3.61, 1.94–5.13, 1.95–5.39, and 1.86–5.50 mmol/L for low-density lipoprotein cholesterol; 1.11–2.31, 1.30–2.75, 1.24–2.59, and 1.20–2.65 mmol/L for high-density lipoprotein cholesterol; 1.89–4.20, 2.59–5.85, 2.87–6.17, and 2.88–6.78 mmol/L for non-high-density lipoprotein cholesterol; 1.04–1.96, 1.25–2.41, 1.23–2.46, and 1.25–2.47 g/L for apolipoprotein A1; 0.43–0.82, 0.63–1.17, 0.65–1.55, and 0.79–1.77 g/L for apolipoprotein B; and 0.27–0.79, 0.35–0.94, 0.39–1.11, and 0.40–1.15 for the apolipoprotein B and apolipoprotein A1 ratio from the first trimester to the delivery period, respectively. The results of the Hoffman and inverse modelling methods closely aligned with those of the TML method. In pregnant women, lipid levels that deviate above or below the established TSRIs are significantly associated with the occurrence of APOs. Conclusion TSRIs are recommended for the identification and management of dyslipidemia during pregnancy. Inappropriate maternal blood lipid levels are associated with an increased risk of APOs.